2005
DOI: 10.1136/ard.2004.028548
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasound findings in healthy wrists and finger joints before and after use of two different contrast agents

Abstract: Objective: To examine the effect of contrast agents on Doppler ultrasound findings in the synovial membrane in the wrist and fingers of healthy volunteers. Material and methods: Eleven healthy subjects were included in the study (5 women and 6 men, mean age 38 years, range (20-60)). They had no clinical signs of inflammatory or degenerative joint diseases. A total of 66 joints were examined-6 joints for each subject: wrist and metacarpophalangeal (MCP) joints 1-5-before contrast injection and after Levovist an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 11 publications
1
15
1
1
Order By: Relevance
“…As the addition of contrast improves the detection of low-velocity flow through small vessels, by increasing the power within the Doppler signal, an apparent increase in perfusion, even in normal synovium, would be expected in the post-contrast study. A recent report of colour Doppler activity in normal MCP joints (from healthy volunteers) following the injection of two different contrast agents demonstrates this [29]. However, interestingly in our study, in 10 joints (all of which were either T-only, S-only or S þ T) a change from normal (PD grade 0-1) to abnormally increased perfusion indicative of active inflammation (PD grade 2 or 3) was seen following the contrast.…”
Section: Discussioncontrasting
confidence: 50%
“…As the addition of contrast improves the detection of low-velocity flow through small vessels, by increasing the power within the Doppler signal, an apparent increase in perfusion, even in normal synovium, would be expected in the post-contrast study. A recent report of colour Doppler activity in normal MCP joints (from healthy volunteers) following the injection of two different contrast agents demonstrates this [29]. However, interestingly in our study, in 10 joints (all of which were either T-only, S-only or S þ T) a change from normal (PD grade 0-1) to abnormally increased perfusion indicative of active inflammation (PD grade 2 or 3) was seen following the contrast.…”
Section: Discussioncontrasting
confidence: 50%
“…Moreover, Weidekamm et al [23] demonstrated that the decrease of AUC was observed also in cases with persistent PD. Due to the increased sensitivity of CEUS in detecting slow flow and flow in small vessels compared with PD [14,17,37], it is possible that TIC parameters detect the minimal changes in the synovial vascularisation and correlate less with PD [23].…”
Section: Discussionmentioning
confidence: 99%
“…1) [41]. Beim gesunden, nicht entzündeten Gelenk gelingt es im allgemeinen auch mit sehr hoch auflösenden und sensitiven Geräten nur in Ausnahmefällen, die physiologische synoviale Durchblutung darzustellen, so dass der Nachweis einer Vaskularisierung unter Berücksichtigung einer sicheren intraartikulären Lokalisation derselben prinzipiell als pathologisch zu werten ist [46,50].…”
Section: Wieso Funktioniert Doppler Am Gelenk?unclassified